Confronting Confucian understandings of the Christian doctrine of salvation : a systematic theological analysis of the basic problems in the Confucian-Christian dialogue - Huang, Paulos Zhanzhu. (Studies in Systematic Theology, 2009)
A complete exploration is the first systematic analysis ever comparing the central religious doctrinal aspects of Christianity with those in Confucianism. Huang's work carefully covers the whole history of the Confucian-Christian tradition, and ends up with genuinely new insights. He elaborates on the idea of transcendence in the Confucian tradition in a manner which enables an interpretation of the Christian means of salvation. His explanation of transcendence, and its connection with the means of salvation, is new and unique, offering a clue to the special understanding of salvation germane to the specifically Chinese intellecual history. Huang's book is a must for anyone interested in the Sino-Western cultural encounter.